"Hul Topol" - Fall of the Moon A narrative of etiologies from the Bunaq of Lamaknen - Schapper, Antoinette (Wacana, Journal of the Humanities of Indonesia, 2016)
This article makes a contribution to the documentation of the genre of oral literature known as zapal amongst the Bunaq, a Papuan-speaking group of central Timor. I present an annotated and translated version of the elaborate zapal entitled Hul Topol or Fall of the Moon. Hul Topol is a lengthy, multi-event story which gives etiologies spanning the realms of subsistence, cultural practice and natural order including animal behaviour and appearance.